1985
DOI: 10.1002/nur.4770080115
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a husband's chronic illness (COPD) on the spouse's life

Abstract: This study was conducted to determine the impact of a husband's chronic illness on the spouse's life. The sample was 76 married women, 46 whose husbands had a diagnosis of chronic obstructive pulmonary disease (COPD) and 30 whose husbands did not have a chronic illness. On a mailed questionnaire wives of COPD patients reported higher subjective stress (p = .032) and lower life satisfaction (p = .006) than the wives whose husbands did not have a chronic illness. The COPD wives assumed more new roles and respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 28 publications
5
62
1
Order By: Relevance
“…In comparison with patients suffering from terminal lung cancer, health-related quality of life in COPD is even worse (Gore et al 2000;Habraken et al 2009). The patients' disease also impacts their partners' well-being and quality of life (Bergs 2002;Cannon and Cavanaugh 1998;Grant et al 2012;Hynes et al 2012;Kanervisto et al 2007a; Kanervisto et al 2007b;Keele-Card et al 1993;Rees et al 2001;Sexton and Munro 1985). Spouses' health-related quality of life is considerably lower compared to samples similar in age (Kühl et al 2008;Thöne et al 2011), and it tends to be even lower than patients' quality of life (Rees et al 2001).…”
Section: Introductionmentioning
confidence: 94%
“…In comparison with patients suffering from terminal lung cancer, health-related quality of life in COPD is even worse (Gore et al 2000;Habraken et al 2009). The patients' disease also impacts their partners' well-being and quality of life (Bergs 2002;Cannon and Cavanaugh 1998;Grant et al 2012;Hynes et al 2012;Kanervisto et al 2007a; Kanervisto et al 2007b;Keele-Card et al 1993;Rees et al 2001;Sexton and Munro 1985). Spouses' health-related quality of life is considerably lower compared to samples similar in age (Kühl et al 2008;Thöne et al 2011), and it tends to be even lower than patients' quality of life (Rees et al 2001).…”
Section: Introductionmentioning
confidence: 94%
“…This has long been recognised and described as living within an 'emotional straight jacket' with both positive emotions such as laughter, and negative emotions such as anger, leading to distressing dyspnoea (Rabinowitz & Florian, 1992, Dudley et al, 1980, Diethorn, 1985. Partners of COPD patients tend to avoid discussing problems, or subjects that could lead to conflict with their ill spouses, for the same reason (Ring & Danielson, 1997, Sexton & Munro, 1985, Gullick, 2008.…”
Section: Changes In Personality and Moodmentioning
confidence: 99%
“…This loss of intimacy through conversation is parallelled with a loss of physical intimacy, including sexual interaction (Gullick, 2008, Sexton & Munro, 1985. Where intercourse is attempted it may be frightening with distressing breathlessness distracting both partners from the romanticism or eroticism of the moment.…”
Section: The Confining Nature Of Copd For the Patient And Familymentioning
confidence: 99%
“…In addition, the patient's chronic illness may limit the control individuals feel over social interactions, such as when and where these may occur [38]. For example, Sexton and Munro [39] reported that 30.4% of their sample of wives of COPD patients were no longer engaged in social activities because of the patients' illnesses. Haley and colleagues [40] found no differences in size of social support network or number of contacts with family between caregivers and controls.…”
Section: Discussionmentioning
confidence: 99%